2022
DOI: 10.1136/bmjopen-2022-062632
|View full text |Cite
|
Sign up to set email alerts
|

Prospective double-blind randomised controlled trial protocol comparing bone marrow aspirate concentrate intra-articular injection combined with subchondral injection versus intra-articular injection alone for the treatment of symptomatic knee osteoarthritis

Abstract: IntroductionSubchondral and intra-articular injections of bone marrow aspirate concentrate (BMAC) showed promising results for knee osteoarthritis (OA) patients. To date, there is no evidence to demonstrate whether the combination of these treatments provides higher benefits than the intra-articular injection alone.Methods and analysisEighty-six patients with symptomatic knee OA (aged between 40 and 70 years) are randomised to BMAC intra-articular injection combined with subchondral BMAC injection or BMAC intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For this reason, treatments that may reduce disease manifestation in addition to slowing or stopping its progression are actively sought. In this frame, mesenchymal stromal cells (MSCs) have emerged as an attractive option, both as GMP-grade products [ 13 ] and as point-of-care products [ 14 ] such as bone marrow aspirate concentrate (BMAC) [ 15 ], micro-fragmented adipose tissue (MFAT) [ 16 ] or stromal vascular fraction (SVF) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, treatments that may reduce disease manifestation in addition to slowing or stopping its progression are actively sought. In this frame, mesenchymal stromal cells (MSCs) have emerged as an attractive option, both as GMP-grade products [ 13 ] and as point-of-care products [ 14 ] such as bone marrow aspirate concentrate (BMAC) [ 15 ], micro-fragmented adipose tissue (MFAT) [ 16 ] or stromal vascular fraction (SVF) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies on the usage of autologous BMAC injection in KOA showed promising and encouraging results in terms of pain reduction, improved knee range of movement, ease of life's daily activities, and, thus, improved quality of life. These results obtained with autologous BMAC are longer-lasting than other non-surgical treatments and also showed better safety profiles [15][16][17].…”
Section: Introductionmentioning
confidence: 74%
“…Up to now only articles on BMAC injections were published with a short term follow up (6-12-24 months), regardless of the respective joint: 8,9,[15][16][17]19,[28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%